Suppression of Breast Cancer Cell Proliferation by Selective Single-Domain Antibody for Intracellular STAT3. (2nd January 2018) - Singh, Sunanda; Murillo, Genoveva; Chen, Dong; Parihar, Ashutosh S; Mehta, Rajendra G
Background: The serendipitous discovery of heavy-chain antibodies devoid of light chains in camelids and the subsequent development of VHHs (variable region of camelid heavy chain) have provided a very important tool for research and possibly for therapeutics. In this study, we synthesized single-domain 15-kDa antibody SBT-100 (anti-STAT3 B VHH13) against human STAT3 (signal transducer and activator of transcription) that binds selectively to STAT3 and suppresses the function of phosphorylated STAT3 (p-STAT3). Methods: Single-chain VHH nanobodies were generated by immunizing camelid with humanized STAT3. Commercially available breast cancer cell lines including MDA-MB-231, MDA-MB-468, MDA-MB-453, MCF-7, and BT474 were used. Cell proliferation was determined by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. The association of anti-STAT3 B VHH13 with STAT3 and p-STAT3 was determined by immunoprecipitation and Western blot analyses. The efficacy of SBT-100 on the growth of MDA-MB-231 xenografts in vivo was determined using athymic mice. Statistical significance for cell proliferation was determined using analysis of variance. If a significant difference ( P  < .05) was observed, then Tukey-Kramer multiple comparison test was conducted. Results: SBT-100 suppressed cell proliferation of triple-negative breast cancer cells ( P  < .01) as well as provided significant inhibition of tumor growth ( P  < .05) in a xenograft model without any toxicity. Results are presented to show that anti-STAT3 B VHH13 selectively binds to STAT3 suggesting that the effects were mediated by inhibiting STAT3. Conclusions: A very large number of human malignancies and benign diseases have constitutive STAT3 activation. Therefore, the results described here suggest that anti-STAT3 B VHH13 can be developed for therapeutic intervention for cancer cells expressing STAT3 or p-STAT3.